Instant places: using bluetooth for situated interaction in public displays - José, Rui (2008)
Instant Places is an investigation into the role of Bluetooth presence and naming as techniques for situated interaction around public displays. Our utilization of Bluetooth naming extends beyond identity representation, introducing the use of a simple instruction mechanism in which the system can recognise parts of the Bluetooth device name as explicit instructions to trigger the generation of pervasive content on situated displays. The study specifically addresses the suitability of these techniques and the type of social practices that emerged from their availability in a real setting. The results of the study, which involved the deployment of a fully functional prototype in a bar for several weeks, suggest that, despite their simplicity, these techniques were effective in their ability to sustain situated interaction around a public display and were easily and creatively appropriated for new forms of social practices.